PERILAKU CARING PERAWAT DIMASA PANDEMI COVID-19 DI RUMAH SAKIT UMUM DAERAH KOTA MAKASSAR - Noer Saudah; Imam Zaenuri; Rini Mustamin; Zaenal Zaenal (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2021)
The purpose of the study: to find out the description of the caring behavior of nurses in the ward of the Makassar City General Hospital. Methods: This study used a descriptive survey using a non-probability sampling technique, namely consecutive sampling. The sample in this study was 77 people according to the inclusion criteria and exclusion criteria. Collecting data using a questionnaire Care Q (the Nurse Behavior Caring Study) based on the opinion of Larson (1998, in Watson 2004). Questionnaire sheet. Results: The results showed that the caring behavior of nurses at the Makassar City General Hospital in general was mostly good (79.2%). , explanation and facilities (79.9 %), comfort (79.9 %), trusting relationship (71.4 %). Discussion: In the application of caring behavior nurses need to integrate various dimensions of caring behavior which include readiness and willingness, explanations and facilities, comfort, mutual trust relationships to improve the quality of nursing services which have an impact on increasing patient satisfaction and decreasing hospital days. Conclusion: Nurse caring behavior in Makassar City General Hospital in general is mostly good Suggestion: Nurses are expected to cultivate a culture of caring for patients by reminding each other among colleagues to improve the quality of nursing services